How Does Mg2+(aq) Interact with ATP(aq)? Biomolecular Structure through the Lens of Liquid-Jet Photoemission Spectroscopy - Mudryk, Karen; Lee, Chin; Tomaník, Lukáš; Malerz, Sebastian; Trinter, Florian; Hergenhahn, Uwe; Neumark, Daniel M; Slavíček, Petr; Bradforth, Stephen; Winter, Bernd (Journal of the American Chemical Society, 2024)
Liquid-jet photoemission spectroscopy (LJ-PES) allows for a direct probing of electronic structure in aqueous solutions. We show the applicability of the approach to biomolecules in a complex environment, exploring site-specific information on the interaction of adenosine triphosphate in the aqueous phase (ATP(aq)) with magnesium (Mg2+(aq)), highlighting the synergy brought about by the simultaneous analysis of different regions in the photoelectron spectrum. In particular, we demonstrate intermolecular Coulombic decay (ICD) spectroscopy as a new and powerful addition to the arsenal of techniques for biomolecular structure investigation. We apply LJ-PES assisted by electronic-structure calculations to study ATP(aq) solutions with and without dissolved Mg2+. Valence photoelectron data reveal spectral changes in the phosphate and adenine features of ATP(aq) due to interactions with the divalent cation. Chemical shifts in Mg 2p, Mg 2s, P 2p, and P 2s core-level spectra as a function of the Mg2+/ATP concentration ratio are correlated to the formation of [Mg(ATP) 2]6-(aq), [MgATP]2-(aq), and [Mg2ATP](aq) complexes, demonstrating the element sensitivity of the technique to Mg2+-phosphate interactions. The most direct probe of the intermolecular interactions between ATP(aq) and Mg2+(aq) is delivered by the emerging ICD electrons following ionization of Mg 1s electrons. ICD spectra are shown to sensitively probe ligand exchange in the Mg2+-ATP(aq) coordination environment. In addition, we report and compare P 2s data from ATP(aq) and adenosine mono- and diphosphate (AMP(aq) and ADP(aq), respectively) solutions, probing the electronic structure of the phosphate chain and the local environment of individual phosphate units in ATP(aq). Our results provide a comprehensive view of the electronic structure of ATP(aq) and Mg2+-ATP(aq) complexes relevant to phosphorylation and dephosphorylation reactions that are central to bioenergetics in living organisms.
Keywords: fotoelektronová spektroskopie; Magnesium; Photoelectron Spectroscopy; Adenosine Triphosphate; adenosintrifosfát; hořčík